PELATIHAN TANGGAP BENCANA, TERAPI MENULIS EKSPRESIF DAN RELAKSASI UPAYA PENURUNAN KECEMASAN PADA ANAK PASCA BENCANA TANAH LONGSOR DI PONOROGO - Kusumawati, Elza; Noviekayati, IGAA; Amanda Pasca Rini, Rr.; Ema Mustikawati, Anrilia (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2024)
Based on statistical data from BNPB for the last 10 years, the frequency of natural disasters in Indonesia has increased, such as floods, landslides and earthquakes. The purpose of this community service is to make SD Sriti 1 Ponorogo students responsive in dealing with disasters, especially landslides that have occurred in October - November 2022. In addition, students are taught relaxation techniques and how to express their feelings when facing landslide disasters. The method used is in the form of disaster response training as a strategy for dealing with disasters and relaxation techniques and writing therapy as an effort to reduce the anxiety experienced by children when facing landslides. The instrument used to measure anxiety is in the form of 4 questions that represent feelings, thoughts, physical responses and moods of children in narrative form as a way for children to express what is being experienced in writing and questions related to children's knowledge about landslides. The results show that children experience an increase in understanding of disaster response and experience a decrease in the anxiety they experience.